Exchange rate crises and capital market imperfections in small open economies - Crowe, Chris (CDB St. MichaelBB, 2000)
Estimates a model derived from 'first generation' accounts of exchange rate crises, using Barbados as a case study. Indicates that the standard 'first generation' model (FGM) should be modified by the addition of dynamics and allowance for capital market imperfections. Notes that the paper is supportive of the view that rapid capital account liberalisation, exchange rate stability and an autonomous monetary policy are not simultaneously attainable.